An Analysis of Electronic Medical Record Implementation at RSUD Tais, Seluma Regency In 2025 - Purnamaliyah Purnamaliyah; Firman Bintara; Jon Hendri Nurdan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Seluma Regency ranks 5th out of 10 regencies/cities, with 31.76% of health care facilities (fasyankes) connected to the Electronic Medical Record (EMR) system. The implementation of EMR still faces various obstacles, such as low compliance and knowledge among officers, limited infrastructure, and suboptimal budget support. The study aims to analyze the factors that influence the implementation of EMR, including staff compliance and knowledge, changes in governance, supporting facilities, and budgetary support. The method used is an analytical research design with a mixed-method approach. Data was collected by distributing questionnaires to 30 respondents consisting of health workers and management of the Seluma District General Hospital using stratified random sampling. This was clarified with a qualitative approach and field observations. The integrated results show that although statistically the variables are not significant, in practical terms, increasing staff knowledge through structured training, providing adequate technological facilities, and strengthening management commitment are seen as strategic steps to improve the achievement of RME implementation. Regular training, structured supervision, and strengthening of facilities and budgets to support RME implementation are recommended. Change management needs to be designed systematically with improved data connectivity. Further research on a larger scale is recommended to strengthen the findings.